Enacting conflict, controversy, and aggression in online spaces - Puschmann, Cornelius; Ford, Heather; Recuero, Raquel; Phillips, Whitney; Sauter, Theresa; Bruns, Axel; Eckert, Stine (AoIR Selected Papers of Internet Research, 2013)
Online spaces have been the sites of conflict and aggressive behavior since the earliest days of the internet, from Usenet, Internet Relay Chat and web forums to Facebook and Twitter (Danet, 1998; Donath, 1999; Herring et al, 2002). While flaming and trolling in digital environments have in the past been the subject of research in a wide range of different fields (communication, anthropology, political science, psychology) attempts to systematically describe and compare different forms of communicative aggression across online spaces and trace their immediate and long-term impacts on the negotiation of power relations and community dynamics remain incomplete and are difficult to generalize beyond specific contexts. Attempting such a description seems particularly relevant in light of efforts to use algorithmic and computational approaches to automatically assess aggressive behavior (Yasseri et al, 2012; Taraborelli and Ciampaglia, 2010) following into a similar direction as sentiment analysis in seeking to quantify particular communicative actions (Kennedy, 2012; Papacharissi & Oliveira, 2012). Such approaches raise serious questions about the heterogeneous and culturally specific nature of aggression, which is deeply rooted in different communities discourses and practices. Research from all areas of study is therefore essential in order to improve understanding of such actions and their implications. This panel brings together scholars from different disciplines using both qualitative and quantitative methods to study conflict in different online environments. It addresses some of the following questions in a series of five paper presentations:- What is considered aggressive behavior in different online environments?- What is the relation between aggressive behavior and controversy?- How is conflict enacted discursively and symbolically?- In what ways does the interaction between cultural and technological aspects shape the characterization of these behaviors?- What is the impact of aggressive behavior in different user communities? $2 , $2 , examines a single case of a long-term editor of the Arabic, English and Hebrew Wikipedias who was eventually blocked indefinitely from the English Wikipedia for edit warring and the evasion of Wikipedia arbitration committee sanctions against him. The author follows the story of the rise and fall of this model Wikipedian and discusses the impact of his experience on our understanding of what Wikipedians are like, why some Wikipedia conflicts can never be resolved and the increasing power of a selected group of arbitrators to administer “justice” on Wikipedia. $2 , $2 , focuses on how memes in Facebook reproduce symbolic violence through stigmatizing social stereotypes in humorous memes. The authors analyse three humor fanpages and their content and cross data with 394 online interviews. Results point to several strategies of reproduction of the stigma through humorous discourse, which are classified as a) legitimation, b) humurous allowance and c) discredit of the critics. The paper furthermore discusses the role that social network sites play in this process through their sociotechnical characteristics. $2 , $2 , presents an analysis of Facebook memorial page trolling, a tactic of self-identifying Facebook trolls who post abusive comments and images onto pages created for and dedicated to the deceased. It draws from extensive participant observation and discusses the complex relationship between platform, community and user behavior. The authors focus specifically on the ways in which trolls’ on-site behaviors both subverts and replicates the behavioral patterns of “legitimate” users — behaviors which are embedded within and necessitated by Facebook’s architecture. $2 , $2 , approaches an ongoing political debate on Twitter. The authors apply a combined quantitative and qualitative methodology to investigate the structural make-up and emotional content of tweeting activity around the hashtag #auspol (for Australian politics) in order to highlight the polarity and conservativism that characterise this highly active community of politically engaged individuals. They document the centralised structure of this particular community which is based around a deeply committed core of contributors, and explore the communicative tone, patterns of engagement and thematic drivers that shape the affective character of the community and its cohesiveness. $2 , $2 , assesses the discursive politics of a public debate that erupted in January 2013 in the German-speaking Twittersphere after a female journalist complained in an interview that a prominent German politician had commented on the size of her bust following a public event. Under the hashtag #aufschrei (#outcry) a group of Twitter users posted personal accounts of sexual harassment and violence they had experienced, providing countless first-hand examples of sexist and discriminatory behavior towards women and girls. The authors conduct a content analysis of a sample of the #aufschrei tweets to demonstrate how online environments can become a stage for the struggle of different actors to define gender as a relevant social category. $2 Danet, B. (1998). Text as mask: Gender, play, and performance on the Internet. In S. G. Jones (Ed.), $2 (pp. 129-158). Thousand Oaks; Ca: Sage.Donath, J. S. (1999). Identity and deception in the virtual community. In M. A. Smith and P. Kollock (Eds.), $2 (pp. 29-59). London: Routledge.Herring, S., Job-Sluder, K., Scheckler, R., & Barab, S. (2002). Searching for Safety Online: Managing “Trolling” in a Feminist Forum. $2 , 18(5), 371–384. doi:10.1080/01972240290108186Kennedy, H. (2012). Perspectives on Sentiment Analysis. $2 , 435–450. doi:10.1080/08838151.2012.732141Papacharissi, Z., & De Fatima Oliveira, M. (2012). Affective News and Networked Publics: The Rhythms of News Storytelling on #Egypt. $2 , 266–282. doi:10.1111/j.1460-2466.2012.01630.xTaraborelli, D., & Ciampaglia, G.L. (2010). Beyond Notability. Collective Deliberation on Content Inclusion in Wikipedia. Fourth IEEE International Conference on Self-Adaptive and Self-Organizing Systems Workshops (SASOW '10).Yasseri, T., Sumi, R., Rung, A., Kornai, A., & Kertész, J. (2012). Dynamics of conflicts in Wikipedia. $2 , e38869. doi:10.1371/journal.pone.0038869